Overcoming Gender Bias in STEM: The Effect of Adding the Arts (STEAM) - Clara Wajngurt; Pessy J. Sloan (Park University, 2019)
This study investigated female students who attended a STEM course with the Arts (STEAM) in comparison to a traditional STEM course and the impact it had on desire to pursue a STEM degree. An independent-samples t-test was conducted to compare female to male students' interest in pursuing STEM degrees. In addition, follow up data for registration in STEM subjects was calculated. The participants (N = 58) consisted of college students (35 female students and 23 male students) attending a postsecondary institution in the northeastern United States. The study found significant differences (p < .05) between the groups and a larger percentage of female students from the STEAM course than from the traditional STEM course enrolled in another STEM course at follow up. These results support the positive relationship between female students attending a STEAM course and desire to pursue a STEM degree. The implications and results of adding interdisciplinary elements to traditional STEM courses for female students are discussed.